Alpha-fetoprotein response following transarterial chemoembolization indicates improved survival for intermediate-stage hepatocellular carcinoma. Issue 1 (January 2019) - Liu, Guanghua; Ouyang, Qiang; Xia, Fang; Fan, Guoping; Yu, Juming; Zhang, Caiyuan; Wang, Dengbin
Abstract: Background: To investigate the clinical value of the alpha-fetoprotein (AFP) response following transcatheter arterial chemoembolization (TACE) in intermediate-stage hepatocellular carcinoma (HCC). Methods: Data on patients with Barcelona Clinic Liver Cancer B staging system were analyzed. An AFP response was defined as a decrease in AFP of more than 20% after a TACE session. The association between AFP response and treatment outcome regarding imaging response and overall survival (OS) was explored. Cox proportional hazards models were applied to identify independent risk factors for OS after TACE. Results: Of the enrolled 376 patients with elevated serum AFP >20 ng/mL, 214 (57%) with AFP responses were identified. AFP responders had improved median survival than non-responders (20 vs. 12 months, P  = 0.002). AFP response was significantly correlated with imaging response ( P  < 0.001). The Cox proportional hazards model revealed that AFP response was an independent factor for OS (hazard ratio, 0.59; 95% confidence interval, 0.45–0.78; P  < 0.001). In stratified analyses, an AFP response achieved improved survival in patients with tumor diameters ≤5 cm, diameters >5 cm, tumor number ≤3 and without underlying cirrhosis. Conclusions: The AFP response indicates enhanced survival after TACE in patients with intermediate-stage BCLC.